EmmPack 1.01: C/C++ Code for Use with Ox for Estimation of Univariate Stochastic Volatility Models with the Efficient Method of Moments - Pieter J. van der Sluis (Tinbergen Institute, 1998)
Econometric estimation using simulation techniques, such as the efficient method of moments, may betime consuming. The use of ordinary matrix programming languages such as Gauss, Matlab, Ox or S-plus will very often cause extra delay. For the Efficient Method of Moments implemented to estimatestochastic volatility models this will surely be the case. Therefore the author made a C/C++ librarycontaining the bulk of the procedures needed in the implemention of the efficient method of momentstechnique for a broad range of univariate stochastic volatility models. As a side effect of the EfficientMethod of Moments, EGARCH models with a variety of nonnormal distributions can be estimatedwith this package. Implementations have been made for the Intel Pentium platform under Windows andfor the IBM RS/6000 platform under AIX. The library is dynamically linked to Ox under Windows andstatically under AIX. The speed improvements are considerable compared with pure Ox code. Thepaper serves as a manual for this library. It describes the efficient method of moments for this specificcase of stochastic volatility models. It describes the program. Some examples are given from other workof the author. Technicalities are given in the appendices.
Keywords: 330; Volatilität; Schätztheorie; Theorie